The Benefits of Supplementary Fat in Feed Rations for Ruminants with Particular Focus on Reducing Levels of Methane Production - Rasmussen, J. (International Scholarly Research Network, 2011)
Methane (CH(4)), a highly potent greenhouse gas, has repeatedly been identified as a significant contributor to global warming. In this connection, ruminants, animals that produce large quantities of methane, have been singled out as an area for reduction with regard to their emissions to the atmosphere. In an analysis of recently published data, we identify the underlying mechanisms of methane production in ruminants and focus on the efficacy of different fat sources in terms of their ability to reduce methane production. Specific attention has been placed on in vivo studies involving cattle and sheep, as well as studies based on a large number of animals (>10), recorded over a longer period (>21 days), and employing reliable techniques for the quantification of methane production. Data clearly indicate that supplementary fat, given to ruminants inhibits methane production, with medium-chain fatty acids (laurin, myristic acid) as well as poly-unsaturated fatty acids (linoleic and especially linolenic acid) having a significant effect. It is also apparent that conflicting findings between individual published trials can largely be resolved when one takes into consideration differences in experimental design, the composition of the basic feeds, the fat sources used, and the number of animals involved.